Rapid, simultaneous, and in situ authentication and quality assessment of intact bell peppers using near‐infrared spectroscopy technology. (17th October 2018) - Sánchez, María‐Teresa; Torres, Irina; de la Haba, María‐José; Chamorro, Ana; Garrido‐Varo, Ana; Pérez‐Marín, Dolores
Abstract: BACKGROUND: The ability of near‐infrared (NIR) spectroscopy to authenticate individual bell peppers as a function of the growing system (outdoor or greenhouse) was tested using partial least squares discriminant analysis. Bell peppers grown outdoors (130 samples) or in a greenhouse (264 samples) during the 2015 and 2016 seasons were selected for this purpose and analysed using a portable, handheld, microelectromechanical system (MEMS) instrument MicroPhazir (spectral range 1600–2400 nm), working in reflectance. Subsequently, the potential of NIR spectroscopy as a non‐destructive sensor for in situ quality (dry matter and soluble solid content) measurements, was investigated. RESULTS: The models correctly classified 89.73% and 88.00% of the samples by growing system, when trained with unbalanced and balanced sets respectively, mainly due to the differences in physical–chemical attributes between bell peppers cultivated in the two growing systems. Separate classification models for bell peppers grouped by ripeness (judged by the colour), allowed the classification of 88.28–91.37% of the samples correctly. The standard error of cross‐validation values for the quantitative models were 0.66% fresh weight and 0.75 °Brix for dry matter and soluble solid content, respectively. CONCLUSIONS: The results showed that NIR spectroscopy can be used successfully for predicting the growing systems used in bell pepper production, which is of particular value to guarantee the authentication of outdoor‐grown peppers. Additionally, the results showed that NIR spectroscopy can be used simultaneously as a rapid preliminary screening technique to measure quality. © 2018 Society of Chemical Industry